By design : planning research on higher education - Light, Richard J. (MIT, 1990)
Why do research on higher education? What are your questions? Correlation versus causation What groups do you want to study Specifying the target population Where should you conduct the study? Selecting your sample What predictors do you want to study? The important role of variation Compared to what? Randomized control groups: The best comparisons What are your outcomes? Short-term versus long-term effects How can you improve your measures? Reliability and measurement error Six strategies for improving measurement quality How many people should you study? Instrument precision and sample size Should you try it out on a small scale? The advantages of pilot studies Where should you go from here? Planning a longer-term research program